PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN PENDIDIKAN PANCASILA SISWA KELAS V SDN l LEMING - Hafiza, Raudatul; Husni, Muhammad; Ramdan, Ahmad Yasar; Sururuddin, Muhammad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to determine whether the Problem-Based Learning (PBL) model affects fifth-grade students’ critical thinking skills in Pancasila Education at SDN 1 Leming. The research employed a quantitative pre-experimental approach with a one-group pretest–posttest design. The sample consisted of 33 fifth-grade students selected through purposive sampling. Data were collected using tests and observations. Data normality was tested using the Shapiro–Wilk test at a significance level of ? = 0.05, indicating that the data were normally distributed. The results showed an increase in the mean score from 55.97 (pretest) to 76.79 (posttest). Hypothesis testing using the paired samples t-test (SPSS version 25) indicated that tcalculated > ttable (?8.132 > ?1.694) and a significance value of 0.000 < 0.05. These findings indicate that the Problem-Based Learning model has a significant effect on improving students’ critical thinking skills. In conclusion, the PBL model is effective in enhancing critical thinking skills in Pancasila Education among fifth-grade elementary students.